Signaling through regulated transcription factor interaction: mapping of a regulatory interaction domain in the Myb-related Bas1p - Pinson, Benoît (Oxford University Press, 2000)
Gene activation in eukaryotes is inherently combinatorial depending on cooperation between different transcription factors. An example where this cooperation seems to be directly exploited for regulation is the Bas1p/Bas2p couple in yeast. Bas1p is a Myb-related transcription factor that acts together with the homeodomain-related Bas2p (Pho2p) to regulate purine and histidine biosynthesis genes in response to extracellular purine limitation. We show that fusion of the two factors abolished adenine repression, suggesting that what is regulated by adenine is the Bas1p–Bas2p interaction. Analysis of Bas1p deletions revealed a critical domain (Bas1p interaction and regulatory domain, BIRD) acting in two-hybrid assays as an adenine-dependent Bas1p–Bas2p interaction domain. BIRD had a dual function, as an internal repressor of a centrally located Bas1p transactivation domain on the ADE1 promoter and as a Bas2p-dependent activator on the HIS4 promoter. This promoter-dependent behavior reflected a differential binding to the two promoters in vivo. On ADE1 Bas1p bound the promoter efficiently by itself, but required adenine limitation and Bas2p interaction through BIRD for derepression. On HIS4 efficient promoter binding and derepression required both factors and adenine limitation. We propose a promoter-dependent model for adenine regulation in yeast based on controlled Bas1p–Bas2p interactions through BIRD and exploited differentially by the two promoters.